K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a,\(\left(77.54-54.75\right):54-3^5:3^3\)

\(=[54.\left(77-75\right)]:54-3^2\)

\(=[54.2]:54-9\)

\(=108:54-9=2-9=-7\)

b,\(|-12|+\left(-23\right)+\left(-15\right)+|-7|+9\)

\(=12+\left(-23\right)+\left(-15\right)+7+9\)

\(=-10\)

c,\(4^2+2^3.\left(168:2^2-6^2\right)\)

\(=16+8.\left(168:4-36\right)\)

\(=24.\left(42-36\right)=24.6=144\)

d,\(-35+17+\left(-45\right)+|-13|\)

\(=\left(-35+-45\right)+\left(17+13\right)\)

\(=-80+30=-50\)

HTDT

2 tháng 1 2020

a. 8x+2x =25. 2 mũ 2

8x+2x=100

(8+2)x=100

10x=100

x=100:10

x=10

b.5x+2x=35

(5+2)x=35

7x=35

x=35:7

x=5

25 tháng 10 2017

a)  27^16 : 9^10

Ta có: (3.9)^16 : 9^10

        = 3^16.9^16: 9^10

        = 3^16. 9^6

        = 3^16.(3^2)^6

       =3^16.3^12

       =3^28

17 tháng 10 2016

đây là cách giải của mk:

a, 5(x + 35) = 515

=> x + 35 = 515 : 5

=> x + 35 = 103

=> x        = 103 - 35

=> x        = 68

b, 12x - 33 = 32 . 33

=> 12x - 33 = 32 + 3

=> 12x - 33 = 35

=> 12x - 33 = 243

=> 12x       = 243 + 33

=> 12x       = 276

=>    x       = 276 : 12

=>    x       =  23

c, 6 . x - 5 = 9

=> 6 . x    = 9 + 5

=> 6 . x    = 14

=>     x    = 14 : 6

=>     x    = \(\frac{2}{3}\)

d, 4(x - 12) + 9 = 17

=> 4(x - 12)     = 17 - 9

=> 4(x - 12)     = 8

=> 4 . x - 12    = 8

=> 4 . x           = 8 + 12

=> 4 . x           = 20

=>     x            = 20 : 4

=>     x            = 5

17 tháng 10 2016

a, 5 ( x + 35 ) = 515

x + 35 = 515 : 5

x + 35 = 103

      x = 103 - 35

      x = 68

b, 12x - 33 = 3. 33

12x - 33 = 35

12x - 33 = 243

12x = 243 + 33

12x = 276

x = 276 : 12

x = 23

c, 6.x - 5 = 9

6x = 9 + 5

6x = 14

x = 14 : 6

x = \(\frac{7}{3}\)

d, 4.( x - 12 ) + 9 = 17

4 . ( x - 12 ) = 17 - 9

4 . ( x - 12 ) = 8

x - 12 = 8 : 4

x - 12 = 2

x = 2 + 12

x = 14